Relationship between Air Quality and the Incidence of Respiratory Diseases in the municipality of San José de Cúcuta, Norte de Santander (2021)
Air pollution is one of the most significant environmental problems regarding public health in Colombia. Therefore, the objective of this study was to analyze the relationship between air quality and the incidence of respiratory diseases in the municipality of Cucuta. Through the application of a quantitative and descriptive methodology with a correlational approach, a Citizen Perception Survey was designed. Besides, the concentrations of particulate matter (PM10) in areas from El Salado and Atalaya were analyzed, along with the analysis of the burden of disease according to the records provided by (IMSALUD) and (IDS). The results show a dependent association between the study variables. Additionally, it shows a significant trend for acute Rhinopharyngitis in vulnerable patients (children and older adults) and an unfavorable air quality status of the evaluated months (May-July/2018)